Design and Development of the Board Game “A Perfect Life” to Promote Understanding of Thai Society - จันทร์แจ้ง, พสุกิตติ์; ขันธหัตถ์, ธนภัทร์; กาละปุก, นวกรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
At present, Thai society—particularly in urban areas such as Bangkok—is facing complex problems spanning economic, social, political, and cultural dimensions, which directly affect the quality of life of its people. Youth and students, in particular, often lack a deep understanding of their roles, responsibilities, and the real-life consequences of these societal issues. Traditional learning approaches that rely heavily on lectures or textbook-based instruction may no longer be sufficient to foster awareness and the essential skills required in the 21st century. Therefore, this research aims to design and develop a board game titled “A Balanced Life” (Chiwit Dee Dee Tee Long Tua) as a new learning tool that simulates real-world social scenarios. The game encourages players to think critically, analyze, plan, and make decisions in contexts that closely resemble everyday life. The ultimate goal is to enhance understanding of Thai social issues and instill a sense of responsible life planning through meaningful gameplay.This qualitative research adopts information derived from studies on Thailand’s economic, social, and cultural challenges. The content is transformed into game elements that encourage players to become aware of their societal roles and responsibilities. The development process included document analysis, game design based on Experiential Learning and Game-Based Learning principles, and the creation of three card types: Character Cards, Event Cards, and Support Cards. These elements were structured to align with experiential learning models. Additionally, the game’s graphic design reflects the identity of Bangkok through visual elements, and the prototype was reviewed by board game experts before being tested with a sample group of 50 high school and university students at the "Open House 2025" event at Thonburi University. The study used purposive sampling, observation, and questionnaires to collect data from the gameplay trial.The research findings show that players expressed high satisfaction with the game, particularly in terms of enjoyment, clarity, and design quality. Moreover, players were able to connect the game content with real-life situations, leading to reflective thinking on social roles, life skills, and the complexities of urban living. Participant feedback indicated the need for adjustments in character balancing and clarity in game rules. In conclusion, “A Balanced Life” board game proves to be a promising educational tool for enhancing understanding of social issues in Thailand. It provides an accessible, engaging, and experiential platform that encourages meaningful learning through active participation and social interaction.